Efforts to Improve Fine Motor Skills of 4-5 Year Old Children Through Busy Book Learning Media - Restu Mega Yuliani; Munir Yusuf; Eka Poppi Hutami; Subhan; Pertiwi Kamariah Hasis (UNIB Press, 2025)
This study was motivated by the suboptimal development of fine motor skills in children aged 4-5 years at Paramata Bunda Kindergarten, Palopo City. These children experience difficulties in doing tasks that require eye-hand coordination, such as crumpling paper, buttoning, and opening zippers. The purpose of this study was to improve children's fine motor skills by utilizing the Busy Book as a learning medium. This study employed the Classroom Action Research (CAR) methodology, based on the Kemmis and Taggart framework, which consisted of two cycles, each comprising four sessions. The research participants consisted of 11 students from class A2 (Tomat A). Data collection methods included observation, interviews, documentation, and assessment. The study's results showed a significant improvement in children's fine motor skills after they used the Busy Book systematically and regularly. At the end of the second cycle, six children were included in the